Pengaruh Penambahan Variasi Kulit Buah Naga Merah terhadap Kualitas Selai Buah Naga Merah - Additya Amanda; Iswendi Iswendi (Lembaga Yasin AlSys, 2025)
This study aims to evaluate the effect of varying additions of red dragon fruit peel (Hylocereus polyrhizus) on the quality of red dragon fruit jam, assessed through moisture content, vitamin C content, pH level, and organoleptic characteristics. The jam was formulated in three treatments: without peel, with the addition of 125 grams of peel, and with 250 grams. An experimental method was employed to measure changes in the composition and physicochemical properties of the jam. The results show that the addition of red dragon fruit peel increased moisture content from 26% to 39% and vitamin C content from 1.584% to 2.024%, while decreasing the pH from 4.9 to 4.4. Organoleptic tests revealed that the addition of 250 grams of peel yielded the highest scores for texture and taste attributes, whereas the characteristic aroma of dragon fruit was more pronounced in the jam without peel. These findings indicate that utilizing red dragon fruit peel positively impacts nutritional value, sensory characteristics, and the potential shelf life of the product. The implications of this study support the use of dragon fruit peel waste as an additive in the development of functional food products that are both economically valuable and environmentally sustainable.